Analysis of Elderly Health Status through Intrinsic Capacity Assessment Using the Simple Elderly Screening (SKILAS) Instrument in the Community - Dian Geumala Hayati; Sudijanto Kamso (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Maintaining the health of the elderly is a challenge today, considering that increasing age is generally accompanied by a decrease in functional abilities and health status.One of the preventive efforts to detect a decline in functional capacity is to conduct screening. Screening aims to identify possible risk factors and provide an assessment for further treatment. This study aimed to analyze the health status of the elderly through intrinsic capacity assessment using Simple Elderly Screening (SKILAS) instrument. This screening can assess the decline in intrinsic capacity and then provide specific interventions so that this decline can be slowed down. The data was taken from the routine report of the elderly program of the Tangerang City Health Office from January to February 2024 for 3942 elderly . The sample was taken by purposive sampling in 5 Puskesmas with the criteria that the health center had received training and had conducted SKILAS screening. Data were obtained from the results of screenings conducted by elderly program managers at health facilities or Posyandu. The visiting elderly were assessed for independence function using the Activity Daily Living (ADL) instrument and continued with intrinsic capacity screening using the SKILAS instrument. The results of screening showed that 3771 (95.7%) have a good level of independence. The results of simple elderly screening showed 26 elderly (0.94%) have symptoms of depression, 65 elderly (1.65%) experienced the risk of cognitive decline, 120 elderly (3.04%) experienced limited mobilization, 142 elderly (8.22%) experienced malnutrition, 225 elderly (10.16%) experienced visual impairment and 15 elderly (0.38%) experienced hearing loss. It is recommennded that all elderly people receive SKILAS screening to detect early decline in instrinsic capacity.Keywords: Elderly, Intrinsic capacity, Screening